Smart Cities as a Local Government Innovation and Governance Reform Agenda: A Bibliometric and Systematic Literature Review - Edem Lekettey; Nugraha Nugraha; Maya Sari; Denny Andriana (Dinasti International Journal of Education Management and Social Science, 2026)
Smart city initiatives have rapidly increased; however, existing literature is fragmented across technological, urban planning, and governance frameworks. This study examined smart city research within the framework of local government innovation and governance reform. This research employed an integrated review strategy that combines bibliometric analysis with a PRISMA-compliant systematic literature review, analyzing 482 peer-reviewed journal articles indexed in Scopus to outline the field's history, intellectual framework, and thematic structure. The results indicate a notable transition from technology-focused narratives to frameworks that emphasize governance and public value. Smart cities should be regarded as socio-technical governance systems that utilize digital platforms to improve citizen engagement, policy development, and service delivery. Institutional capability, regulatory alignment, and organizational learning enable the transformation of digital investments into enduring public benefits. This study presents a capability-oriented framework for the analysis of smart city performance and situates urban digital transformation within decentralized local self-governance systems.